A new species of arboreal forest-dwelling gecko (Hemidactylus: Squamata: Gekkonidae) from coastal Kenya, East Africa - Malonza, Patrick K.; Bauer, Aaron M. (Zootaxa, 2014)
A new species of Hemidactylus, H. mrimaensis sp. nov., is described from coastal kaya forests of Kenya. This small-sized, arboreal gecko may be distinguished from its probable close relative, the sympatric H. mabouia, by its more slender habitus, golden color, small adult body length (maximum SVL 50 mm in females) and features of scalation including keeled dorsal tubercles in 11–14 longitudinal rows, pointed tubercles on tail larger than those on the dorsum, and 32–34 precloacal pores in males. This gecko may be endemic to the coastal forests and given the ongoing threats to this habitat, the species is of high conservation concern.